150k views
0 votes
Please help me its timed -H.M​

Please help me its timed -H.M​-example-1

1 Answer

5 votes

Answer:

f(3) = g(3)

General Formulas and Concepts:

Algebra I

Functions

  • Function Notation
  • Graphing

Explanation:

We can see from the graph that the lines intersect at (3, 6). If this is the case, then that means that when x = 3 for both functions, it outputs f(x) = 6.

Rewriting this in terms of function notation:

f(3) = 6, g(3) = 6

∴ f(3) = g(3)

User Luis Montoya
by
4.9k points